Things that go bump in the night! - Dezago, Todd (Marvel super hero squad (Spotlight (Firm)), 2011)
When a Fractal turns a paleontologist into a dinosaur, Speedball joins the squaddies in the Savage Land to stop him from commanding the dinosaurs to take over the world.